Introduction to the Special Series on Behavioral Disorders and Juvenile Justice: Facilitating Effective Reentry Into School and Community. (May 2021) - Griller Clark, Heather; Mathur, Sarup R.
This introduction to the special series on facilitating effective reentry into school and community for youth from the juvenile justice (JJ) system highlights several important issues for educators and others serving youth with emotional and behavioral disorders (EBD). The articles within this special series focus on key factors in programming and professional development that promote reentry success. Central to this discussion are protective factors, like self-determination and engagement, facility programming and climate, provision of person-centered supports, prioritization of youth development and mental health, increased communication and capacity building among stakeholders, and shifting to the use of positive youth outcomes in addition to recidivism as measure of reentry success. Findings and discussion provide a critical reference point for professionals and scholars interested in promoting reentry success and may improve interventions and services for JJ-involved youth, especially those with EBD.